Nonlinear ellipsoid based attitude control for aggressive trajectories in a quadrotor: Closed-loop multi-flips implementation. (August 2018) - Oliva-Palomo, Fatima; Sanchez-Orta, Anand; Castillo, Pedro; Alazki, Hussain
Abstract: In this paper a model-free continuous nonlinear control law for the attitude of a quadrotor, based on the Attractive Ellipsoid Method and a saturation term, is proposed. This control law allows the vehicle to track aggressive maneuvers, such as multiple flips about the y axis of the body frame, with high angular velocities. The controller is designed through a singularity-free attitude representation based on a unit quaternion and its gains are computed by solving an optimization problem with LMIs. The proposed controller preserves the advantageous characteristics of the Attractive Ellipsoid Method and increases its robustness properties with the fast response of the nonlinear saturation term, minimizing as much as possible the attitude tracking error and assuring its convergence to a small neighborhood around the origin. A numerical study based on simulations is presented to analyze the advantages of the proposed approach, and experiments are presented to show the performance of the closed-loop system for tracking aggressive multiple flips, even in outdoors.